1991
DOI: 10.1111/j.1095-8649.1991.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and larval development of brown trout, Salmo trutta L.: exposure to aluminium, copper, lead or zinc in soft, acid water

Abstract: Freshly fertilized ova, eyed ova and yolk-sac fry of brown trout, Salmo truifa L., were exposed to each of four trace metals (aluminium: 6000 nmol I -I ; copper: 80 nmol I-'; lead: 50 nmol I-'; zinc: 300 nmol I-I) while held in flowing artificial soft-water media maintained at pH 4.5 or 5.6 and [Ca] 20 or 200 pmol I-'. In continuous exposure from fertilization, survival of ova was severely affected at pH 4.5 and [Ca] 20 pmol I -I , regardless of the presence of Cu, Pb or Zn; A1 reduced embryonic mortality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
3

Year Published

1993
1993
2003
2003

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 25 publications
2
42
1
3
Order By: Relevance
“…In that study, whole-body potassium concentrations of eyed eggs remained unaffected, and it is possible that the uptake of other minerals may be increased to compensate for sodium loss. No differences in whole-body sodium, potassium, calcium or magnesium concentrations were recorded for brown trout eggs maintained in soft (20 Ixmol 1-1 calcium), acid (pH 4.5) media with or without copper, zinc, lead or aluminium (Sayer et al, 1991a), although the advanced state of the eggs used in the latter study may explain in part the lack of effect. It is generally accepted that the eyed egg stage is more resistant to the conditions associated with acid water than is the green egg stage (see Mortality section, page 108).…”
Section: Embryonic Developmentcontrasting
confidence: 39%
See 2 more Smart Citations
“…In that study, whole-body potassium concentrations of eyed eggs remained unaffected, and it is possible that the uptake of other minerals may be increased to compensate for sodium loss. No differences in whole-body sodium, potassium, calcium or magnesium concentrations were recorded for brown trout eggs maintained in soft (20 Ixmol 1-1 calcium), acid (pH 4.5) media with or without copper, zinc, lead or aluminium (Sayer et al, 1991a), although the advanced state of the eggs used in the latter study may explain in part the lack of effect. It is generally accepted that the eyed egg stage is more resistant to the conditions associated with acid water than is the green egg stage (see Mortality section, page 108).…”
Section: Embryonic Developmentcontrasting
confidence: 39%
“…There are, however, reports of accelerated incubation times at low pH for brook trout (Trojnar, 1977b;Jordahl and Benson, 1987) and brown trout (Sayer et aL, 1991a), but also experiments where incubation time was independent of treatment for Atlantic salmon (Daye and Garside, 1979) and brown trout (Sadler and Lynam, 1988). Although the majority of reports suggest that incubation is prolonged in acid water, experimental conditions such as water quality, origin of eggs and/or control of temperature vary considerably.…”
Section: Duration Of Incubationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, understanding the toxicities of combinations of metals is not necessarily intractable. Sayer et al (1991c) found that Cu (5 µg · L -1 , 0.08 µM), Pb (10 µg · L -1 , 0.05 µM), and Al (160 µg · L -1 , 5.9 µM) caused brown trout fry mortalities and impaired skeletal calcification in synthetic soft water, but Zn did not (20 µg · L -1 Zn, 0.31 µM; pH ~5.6, 20 µM Ca).…”
Section: Metal Mixturesmentioning
confidence: 99%
“…Copper at sublethal levels have been recognised as a stressor causing immunosuppression in fish (Ellis, 1989) resulting in increased susceptibility to infectious diseases (Mazeaud et al, 1977;Zeliko#, 1993). In fish, copper accumulates in haemopoietic and lymphoietic tissues inhibiting their growth, metabolic activity, fecundity, gonadal development (Sayer et al, 1992), and suppresses the immune activities (Anderson et al, 1989;Hossain & Shari#, 1992). However, the e#ects of sublethal concentrations of metals on integrated physiological processes in fish, such as immunocompetency, are not well understood (Dethlo# & Bailey, 1998).…”
Section: Introductionmentioning
confidence: 97%